Canine and feline rabies in the state of São Paulo – data from the Pasteur Institute of São Paulo, 1999-2012 - Carrieri, M. L.; Achkar, S. M.; Castilho, J. G.; Oliveira, R. N.; Carnieli Jr, P.; Macedo, C. I.; Omoto, T. M.; Takaoka, N. Y.; Kotait, I. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The São Paulo State Rabies Control Program, coordinated by the Pasteur Institute of São Paulo, has been involved in endeavors to improve the epidemiological surveillance of rabies in dogs, cats and bats, particularly in urban areas. Since 1998, when the last case of canine rabies due to antigenic variant 2 occurred in the state, the Institute has received 66,352 canine central nervous system samples, 17,796 samples from cats and 38,133 from bat specimens. Using conventional techniques for rabies diagnosis, 11 dogs, 8 cats and 554 bats were found to be positive for this disease. When molecular techniques, such as antigenic typing and genetic sequencing, were used, antigenic variant 3, which is associated with Desmodus rotundus, was detected in 11 dogs and 7 cats; this variant has also been identified in bat species from the genus Artibeus spp., which has synanthropic habits. Only one cat was positive for variant 4, which is associated with Tadarida brasiliensis. It should be noted that the signs and symptoms of cats and dogs infected by rabies variants associated with bats were quite different from those in dogs infected with variants associated with dogs (variants 1 and 2). In general, symptoms were atypical, the most common clinical picture being that of paralysis and hemorrhagic gastroenteritis, and cases were nearly always isolated. Positive samples from cats and dogs frequently came from animals that had been run over and died. These findings show the importance of maintaining active epidemiological surveillance of cats and dogs and of sending samples for rabies diagnosis, particularly in regions where rabies is known to occur in urban areas.